2022
DOI: 10.1108/mf-03-2022-0105
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric determinants of Bitcoin's wild price movements

Abstract: PurposeThe present work endeavors to explore the potential nonlinear and asymmetric effects of supply fundamental properties of Bitcoin mining process (velocity, size and stock of Bitcoins, cost of production and mining revenue), DJIA, VIX, economic policy uncertainty and Google Trend on the price of Bitcoin (PB).Design/methodology/approachThe authors apply the Nonlinear Autoregressive Distributed lag (NARDL) approach for the period from November 31, 2013 to December 30, 2020.FindingsThe asymmetric effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Blockchain volatility is an influential component that influences behavior intentions for future blockchain adoption in the retail industry (Veerasingam & Teoh, 2023). Similarly, blockchain volatility affects behaviour intention and generates a better behavior intention sensation (Benlagha & Hemrit, 2023). This is consistent with the findings, which show that volatility is a stable state that encourages the usage of blockchain in the retail sector (Trichilli & Boujelbéne, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…Blockchain volatility is an influential component that influences behavior intentions for future blockchain adoption in the retail industry (Veerasingam & Teoh, 2023). Similarly, blockchain volatility affects behaviour intention and generates a better behavior intention sensation (Benlagha & Hemrit, 2023). This is consistent with the findings, which show that volatility is a stable state that encourages the usage of blockchain in the retail sector (Trichilli & Boujelbéne, 2023).…”
Section: Discussionsupporting
confidence: 88%
“…Foroutan and Lahmiri ( 2022 ) reinforced that cryptocurrencies are more erratic and unstable than global stock markets during the COVID-19 pandemic. Furthermore, Benlagha and Hemrit ( 2022 ) suggested that high stock market risk aversion and fear increase the value of Bitcoin; however, Haffar and Fur ( 2022 ) asserted that, except for a bear market, no asset could impact Bitcoin because it is a solitary market.…”
Section: Prior Literaturementioning
confidence: 99%
“…Even if some previous studies estimated the long- and short-run relations (Béjaoui et al 2021 ; Ciaian et al 2016 ), the asymmetric associations were not assumed. To this end, we apply the NARDL model as in prior studies (Gaies et al 2021 ; Rajput et al 2020 ; González et al 2021 ; Benlagha and Hemrit, 2022 ). The NARDL model is an asymmetric extension of the ARDL approach.…”
Section: Quantitative Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Aharon et al (2023) suggest that the decentralized nature of cryptocurrencies creates an inherent level of volatility, often fluctuating by huge amounts within a short period. Further, a large portion of researchers believe that cryptocurrencies cannot provide a safe haven for stocks because the role of cryptocurrency stills depending on the market model and the various political and economic factors (Benlagha & Hemrit, 2023; Bouri et al, 2020; Goodell & Goutte, 2021; Murty et al, 2022; Wen et al, 2022). As argued by Yermack (2015), the speculative nature of traditional cryptocurrencies may result in selling pressure through extreme downturns, reflecting limited effectiveness as a perfect store of value and leadership influence over the volatility of the main stock market indices under different time scales (Kakinaka & Umeno, 2022).…”
Section: Introductionmentioning
confidence: 99%